The Implementation of Legal Protection for Migrant Workers in Indonesia - Prasasti, Ashyfa; Nugroho, Wahyu; Fahririn (Veteran Law Review, 2024)
Indonesia as a country with a large population causes an increase in the number of workers that is not accompanied by the availability of jobs. So that many workers migrate to get workers, one of which is abroad. Migrant workers who are abroad need legal protection to avoid violations of the law such as physical violence, sexual harassment, unpaid wages, and many others. For this reason, the Indonesian government has formed Law Number 18 of 2017 concerning the Protection of Indonesian Migrant Workers as an effort to protect its citizens. This study uses qualitative methods and data collection using literature studies. The data used are in the form of journals, proceedings, books, and other related literature that support the problems discussed in this study.